Exploring Difficulties in English Speaking Skills Among Eleventh Grade Students - aldi, Amrullah Sholahuddin; Thoyyib Shof, Ahmad (Darussalam English Journal (DEJ), 2024)
The research was conducted at MA Kanjeng Sepuh Sidayu with the aim of assessing the difficulties students face in speaking English and identifying contributing factors. It employed a qualitative descriptive research approach, focusing on eleventh-grade students. The research sample consisted of 21 students from the science class. Data were collected using two instruments: tests and questionnaires. The test involved a monologue and dialogue-based assessment under the topic of ‘Asking and Giving Opinions.’ After completing the test, the questionnaires, comprised 9 questions covering fluency, pronunciation, grammar, and comprehension ,were given to the students to find out the factors difficulty in sepaking. The findings revealed that students encounter challenges in various aspects of speaking English, including fluency, pronunciation, and vocabulary. Factors such as limited practice, nervousness, and psychological and environmental influences contribute to these difficulties. Keywords : Students Difficulties, Speaking Skill, Factors.